2022
DOI: 10.1155/2022/9184786
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Suitable Landfill Sites for Energy Generation from Municipal Solid Waste: A Case Study of Jabodetabek Area, Indonesia

Abstract: Most municipal solid waste (MSW) is found to be dominated by organic debris, which has excellent potential as an energy source. However, the main problems of this material are poor planning, urban expansion, and lack of management skills. All these problems are presently being encountered by the regional governments of Jakarta, Bogor, Depok, Tangerang, and Bekasi city (known locally as Jabodetabek), Indonesia. In the MSW management system, a vital planning protocol is reportedly assessing suitable landfill sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…According to the latest research [2,19], landfill waste management in Indonesia has three main problems: (a). The traditional waste management system with 'ground cover,' namely by collecting, transporting, and disposing of waste, is no longer effective; and b).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…According to the latest research [2,19], landfill waste management in Indonesia has three main problems: (a). The traditional waste management system with 'ground cover,' namely by collecting, transporting, and disposing of waste, is no longer effective; and b).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Slope is an important criterion in dumpsite selection, as it determines the runoff of the site [31]. A mild slope of less than 12% is suitable for dumpsites [32], as steep slopes increase excavation costs and leachate pollution [31]. A buffer distance of 500 m must be established around rivers or surface water bodies to prevent leachate pollution [33].…”
Section: Methodsmentioning
confidence: 99%
“…Roads and railways are crucial for transporting wastes [34], and the selected site should be away from primary and secondary roads to minimize transportation costs [29,34,35]. Built-up areas should be carefully assessed, as dumpsites can cause harm from various factors, including odors, noise, and health issues [32]. A distance of more than 1000 m is considered appropriate [36].…”
Section: Methodsmentioning
confidence: 99%
“…[34] reported that landuse/landcover was found to be the most influential factor in WtE facility siting while slope was the least influential factor. Conversely, [35] reported that the distance to river was the most important factor in determining a suitable landfill location for energy generation in Jabodetabek Area of Indonesia. However, [36] found that based on economic/technical and socio-cultural criteria, potential sites for locating WtE facilities in Lom´e of Togo are more influenced by slope and residence criteria.…”
Section: Weighting Of the Criteria For Siting Wte Facilitymentioning
confidence: 98%
“…Certain distance should be set apart from the WtE plant in order to reduce the various effects of pollutants associated with the plant operations on the natural environment [40]. Distance from waterbody is a significant criterion in siting WtE facilities to prevent pollution and contamination of waterbody [35]. Figure 3d and Table 6 reveal that locations at a distance of ≤600 meters from waterbody (rivers and streams) are highly suitable while those locations at a distance of ≤100 meters from waterbody are not suitable for WtE facility.…”
Section: Suitability Analysis Of Distance From Waterbodymentioning
confidence: 99%